In vitro evaluation of the reductive carbonyl idarubicin metabolism to evaluate inhibitors of the formation of cardiotoxic idarubicinol via carbonyl and aldo-keto reductases - Bajraktari-Sylejmani, Gzona; Oster, Julia Sophie; Burhenne, Jürgen; Haefeli, Walter E.; Sauter, Max; Weiß, Johanna (Archives of toxicology, 2024)
The most important dose-limiting factor of the anthracycline idarubicin is the high risk of cardiotoxicity, in which the secondary alcohol metabolite idarubicinol plays an important role. It is not yet clear which enzymes are most important for the formation of idarubicinol and which inhibitors might be suitable to suppress this metabolic step and thus would be promising concomitant drugs to reduce idarubicin-associated cardiotoxicity. We, therefore, established and validated a mass spectrometry method for intracellular quantification of idarubicin and idarubicinol and investigated idarubicinol formation in different cell lines and its inhibition by known inhibitors of the aldo-keto reductases AKR1A1, AKR1B1, and AKR1C3 and the carbonyl reductases CBR1/3. The enzyme expression pattern differed among the cell lines with dominant expression of CBR1/3 in HEK293 and MCF-7 and very high expression of AKR1C3 in HepG2 cells. In HEK293 and MCF-7 cells, menadione was the most potent inhibitor (IC50 = 1.6 and 9.8 µM), while in HepG2 cells, ranirestat was most potent (IC50 = 0.4 µM), suggesting that ranirestat is not a selective AKR1B1 inhibitor, but also an AKR1C3 inhibitor. Over-expression of AKR1C3 verified the importance of AKR1C3 for idarubicinol formation and showed that ranirestat is also a potent inhibitor of this enzyme. Taken together, our study underlines the importance of AKR1C3 and CBR1 for the reduction of idarubicin and identifies potent inhibitors of metabolic formation of the cardiotoxic idarubicinol, which should now be tested in vivo to evaluate whether such combinations can increase the cardiac safety of idarubicin therapies while preserving its efficacy.
Gesehen am 22.03.2024